GE_GERICHTE C/24584/2021 vom 24. Mai 2024 - GE Cour de justice (2024)
DIVORCE;OBLIGATION D'ENTRETIEN;ENFANT;CONJOINT;ATTEINTE À LA SANTÉ;LIQUIDATION DU RÉGIME MATRIMONIAL;PRÉVOYANCE PROFESSIONNELLE | CO.120; CC.124e; CC.125; CC.126; CC.285; CC.286.al3